PENERAPAN MODEL PEMBELAJARANKOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III MI-ALMUHAJIRIN MENGGALA SAKTI KECAMATAN TANAH PUTIH - ', Tarmini; Marhadi, Hendri; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is a Class Action Research (CAR) conducted aims to improve science learning outcomes of students of class III MI Al-Muhajirin by applying the model of cooperative learning type Two Stay Two Stray (TSTS). Formulation of the problem: Does the implementation of cooperative learning model Two Stay Two Stray (TSTS) can improve learning outcomes grade science students III MI Al-Muhajirin Menggala Sakti Tanah Putih Rokan Hilir. This study was conducted on 22 April 2016 until May 13, 2016 with 2 cycles. The subjects were students of class III MI Al-Emigrants are 32 people who used the data source. Data collection instrument in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the results obtained from the study before action replay value with an average of 64.06, an increase in the first cycle with the average being 68.75. In the second cycle increased by an average of 79.68. Activities teachers in the learning process in the first cycle, the first meeting of 66.67%, and a second meeting be 70.83%. At the first meeting of the second cycle 79.17%, and the second meeting increased to 87.5%. The results of the data analysis activities of students in the first cycle of the first meeting and the second meeting 66.67% increase to 75.00%. In the second cycle to the first meeting of 79.17%, and the second meeting increased to 87.50%. The results of the study in class III MI Al-Muhajirin to prove that the implementation of cooperative learning model Two Stay Two Stray (TSTS) can improve learning outcomes grade science students III MI Al-Muhajirin Menggala Sakti. Key Words: Learning Model Two Stay Two Stray (TSTS), IPA Learning Outcomes